Transformation of Community-Based Disability Empowerment Model in Enrekang: An Islamic Perspective - Syamraeni Syamraeni; Fachrul Najamudin; Mudfainna Mudfainna; Tayfur Dereli; Sopian Hadi (Insitut Muslim Cendekia, 2025)
The purpose of the research is to describe the role of IDE Inklusi in strengthening the capacity of disabled people and to analyze the supporting factors for the transformation of ability that changes the paradigm from being mere recipients of assistance to an independent subject. The research method uses a descriptive qualitative approach with data collection techniques through observation and in-depth interviews with IDE Inclusion administrators and members who have become economically independent. The results show that IDE Inclusion succeeded in becoming a successful model of ability transformation by prioritizing Islamic values, as well as revealing that inclusivity requires changes in the role of disabled community in society, beyond mere social awareness. The novelty of this research lies in proving that Islamic values (productive zakat and ukhuwah) can form the foundation of social enterprise operations that are fully managed by persons with disabilities. The implications of the research serve as a reference for Islamic value-based empowerment movements, contribute to the enrichment of the concept of ability transformation through the integration of religious values, and offer recommendations for the governments and religious institutions to adopt similar models.